Part-time work and occupational attainment amongst a cohort of British women - Victoria Prowse (Institute for the Study of Labor (IZA), 2006)
Using data on a cohort of British women who were born in 1958, this paper investigates the effects of qualifications, household structure and family background on the occupational penalty suffered by women in part-time employment. The analysis is conducted using a dynamic multinomial modelling framework in which hours of work and occupational attainment are jointly determined. The results reveal that at the bottom of the occupational hierarchy degree level qualifications improve the occupational attainment of women in part-time employment relative to that of women working full-time. In contrast, at top of the occupational hierarchy, degree level qualifications benefit full-timers more than part-timers. Contrary to the conventional wisdom, women with children have higher occupational attainment than childless women thus suggesting that women with children are relatively selective in terms of the jobs they are willing to accept. Furthermore, women with children experience a smaller part-time occupational penalty than childless women. Family background effects are present but small.
urn:nbn:de:101:1-20090825188
Keywords: 330